Chinese herbal medicine for constipation: zheng-based associations among herbs, formulae, proprietary medicines, and herb–drug interactions. Issue 1 (December 2016) - Zhong, Linda; Zheng, Guang; Ge, Li; Lin, Cheng; Huang, Tao; Zhao, Ling; Lu, Cheng; Lu, Ai; Bian, Zhao
Abstract Background As current symptomatic treatments of constipation are still unsatisfactory, an increasing number of patients seek help from Chinese medicine (CM), particularly Chinese herbal medicine (CHM). This study aimed to review the most frequently used CHM herbs and formulae, proprietary CHMs, and herb–drug interactions for functional constipation usingzheng (syndrome)-based differentiation, and to determine the current practice ofzheng -based CHM treatments for functional constipation. Methods We developed a search strategy to include all the related clinical studies of CHM for constipation and set inclusion and exclusion criteria as studies on subjects with constipation of all ages and both sexes, using objective measures from laboratory or imaging techniques. The interventions included single herbs, CM classical formulae, CM new formulae, and Chinese herb-derived products and combination products. The clinical study types included were quasi- or randomized controlled trials, observational clinical studies, case series or case reports, and other types of appropriate research methods. The data concerning study design, sample size, mode of recruitment, sampling and diagnostic procedure, inclusion and exclusion criteria, and participants' characteristics (including age, sex, and duration of constipation). CM patterns, CM treatment principles, treatment regimen, and CM treatment outcomes were recorded. Results A total of 29, 832 relevant records were found, of which 8541 were duplicate records and 20, 639 were excluded for reasons of irrelevance. The full text of 965 articles was retrieved for detailed assessment, following which 480 articles were excluded for various reasons. From the included articles, we retrieved 190 different CMzheng diagnoses from 485 individual studies. The most commonzheng wasdual deficiency of qi and blood (N = 48), which was diagnosed in 948 out of 15, 740 subjects. The most frequently used classical formula wasMa -Zi -Ren -Wan (MZRW) (N = 75) and the most frequently used proprietary CHM wasRun -Chang -Wan (N = 87) . The most frequently used combined medication wasDa Huang with sodium bicarbonate tablets (frequency across all studies, n = 23), followed byFan Xie Ye with lactulose oral solution (n = 8), Ma -Ren -Ruan -Jiao -Nang with lactulose oral solution (n = 6) andLiu -Wei -An -Xiao -Jiao -Nang (n = 6) with mosapride citrate tablets. Conclusion This study examined the use of CHM for constipation and summarized the herbs, formulae, proprietary medicines, and herb–drug interactions application. These data indicated there were limited information about herb-drug interactions and adverse effects of CHM and further randomized controlled trials with strict design are necessary.